Rural development and migration in northeast syria - Meyer, Günter (Anthropology and Development in North Africa and the Middle East, 2019)
This chapter examines the social and economic impact of the Euphrates Scheme, and in particular two important migration processes attributable to it: These are the resettlement of more than 60,000 people from the upstream reservoir; and the increase in labor emigration from the villages in the Euphrates valley to other Arab countries. It provides an historical overview of the main phases of agricultural development and social change in northeast Syria from 1940 to 1980, which culminated in the realization of the Euphrates Scheme. The chapter analyzes in detail the resettlement of the reservoir people, their socioeconomic structure before the inundation of the Euphrates valley, the factors influencing their choice of different areas of resettlement, and the social and economic situation in the main regions of resettlement. It deals with the problem of labor emigration and focuses on the future prospects of rural development in northeast Syria.
CRIS-Team Scopus Importer:2021-04-20